Intellectual Capital dan Kinerja Keuangan Bank Pembiayaan Rakyat Syariah - Jadzil Baihaqi; Uswatun Muawanah (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
This study aims to examine the effect of intellectual capital on the financial performance, consist of capital, asset quality, earning, liquidity, of Islamic Rural Banks. The data of the research is in the form of secondary data on financial performance information obtained with documentation techniques. Capital performance is measured by CAR, asset quality by NPF, earning by ROA, and liquidity by CR. The population of this study was 163 BPRS throughout Indonesia. We use the purposive-sampling technique and the sample obtained is 26 BPRS in Central Java. The number of sample data is 69 data, for the period 2018-2020. We use the Partial Least Square method in processing data with the help of SmartPLS 3. This study results that intellectual capital affects financial performance (capital, asset quality, and earning), except for liquidity performance.